Pendidikan Karakter dalam Program Ekstrakurikuler Pencak Silat - Mahfuzah, Ahya; Maryono; Muhtar Sofwan Hidayat (STAI AL-AMIN, 2025)
Character education is an important aspect that must be applied in every learning in school, both formally and informally. All elements of the school, including teachers, staff, and other support staff, have a role in shaping the character of students. One method that can be applied is through extracurricular activities, which aim to develop students' talents, interests, and skills outside of academics. At MI Al-Huda Karanggetas, one of the extracurricular activities that focuses on character education is pencak silat. As a native Indonesian martial art, pencak silat not only relies on physical strength but also instills the values of discipline, confidence, cooperation, and a sense of unity. This activity helps students in building a strong mentality and mutual respect. This study uses a qualitative method with a case study approach. Data was collected through observation, interviews, and documentation. Respondents in this study included school principals, pencak silat coaches, and students. The validity of the data is maintained through triangulation of sources and techniques, by comparing the results of interviews from various sources and direct observations in the field. The results of the study show that the pencak silat program has a positive impact on the formation of students' character. Students who participated in this activity showed increased discipline, confidence, and an attitude of respect for diversity and togetherness. With the right strategy, pencak silat has proven to be an effective method in instilling strong character values in students.